x-2/6=-1

Simple and best practice solution for x-2/6=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-2/6=-1 equation:



x-2/6=-1
We move all terms to the left:
x-2/6-(-1)=0
We add all the numbers together, and all the variables
x+1-2/6=0
We multiply all the terms by the denominator
x*6-2+1*6=0
We add all the numbers together, and all the variables
x*6+4=0
Wy multiply elements
6x+4=0
We move all terms containing x to the left, all other terms to the right
6x=-4
x=-4/6
x=-2/3

See similar equations:

| 9x-2=60-3x | | f8=24/8(2) | | 6x+11=11x-10 | | 3x+7/3=5 | | (1/8)^2x=2^-6x | | |3x+9|+|2x-4|=15 | | (.75x-13)(3x-17)=90 | | (.75x-13)3x-17=90 | | 2x-4=3x+-1 | | √2x6=3x-9 | | 2d+83=13=+12d | | X-14x=105 | | -26=-6(3x+8)-14 | | 25x^2+40x-4=0 | | 1.73xX=1.6+X | | 12-3x=4(2+x)+33 | | (2+x)*2=9 | | 2x+1/3x=84 | | 3x2+7=4 | | 1.1x+1.2-5.4=54 | | m=(-2/9)+(11/6) | | -5+25x-40x-1=-4x-8x | | x/3-(2x-1)/4=1 | | (x−4)^2=16 | | 2(3x+4)=5(2x-3) | | 1/2(1-x)=1/3(x-4) | | 4x+8(-3x–8)5x–14;x=9 | | 1/3(6-7a)=30 | | 3/2x+5/4=3 | | -11/3(-5x+1/2)≥-66;x=-5 | | 5p+1=125 | | 2p+1=33 |

Equations solver categories